Pendampingan Diversifikasi Ikan menjadi Frozen Food Berbasis Etnomath-Prenuer bagi Kelompok Ibu Nelayan di Kaduara Barat, Pamekasan - Surahmi, Ema; Nuritasari, Fetty; Aini, Septi Dariatul (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service activity aims to provide assistance in fish diversification to groups of fisherwomen in Kaduara Barat Village, Pamekasan so that they have knowledge on how to process fish into several frozen food products. Frozen food is a method of processing fish-based ingredients into fast food products preserved using a freezing process with the aim of making them last longer, be durable, and maintain their quality. The stages in this activity include; socialization and counseling, assistance in demonstrating the diversification process and the evaluation stage. The products produced are; nuggets, sausages, meatballs, pempek and shredded meat based on ethnomath with the resulting shape containing mathematical concepts, such as geometric shapes (cubes, blocks, prisms, spheres, cylinders and others. This can be called ethnomath-preneur, how to process the potential of local cultural elements in a particular area which involves mathematical concepts that have an entrepreneurial spirit. The results obtained in this activity are the knowledge and skills of partner groups in processing fish into frozen food with high economic value as an effort to increase family income.